Seismic anisotropy and its precursory change before eruptions at Piton de la Fournaise volcano, La Réunion. Issue 5 (25th May 2015) - Savage, M. K.; Ferrazzini, V.; Peltier, A.; Rivemale, E.; Mayor, J.; Schmid, A.; Brenguier, F.; Massin, F.; Got, J.‐L.; Battaglia, J.; DiMuro, A.; Staudacher, T.; et al.
Abstract The Piton de la Fournaise volcano exhibits frequent eruptions preceded by seismic swarms and is a good target to test hypotheses about magmatically induced variations in seismic wave properties. We use a permanent station network and a portable broadband network to compare seismic anisotropy measured via shear wave splitting with geodetic displacements, ratios of compressional to shear velocity (Vp/Vs), earthquake focal mechanisms, and ambient noise correlation analysis of surface wave velocities and to examine velocity and stress changes from 2000 through 2012. Fast directions align radially to the central cone and parallel to surface cracks and fissures, suggesting stress‐controlled cracks. High Vp/Vs ratios under the summit compared with low ratios under the flank suggest spatial variations in the proportion of fluid‐filled versus gas‐filled cracks. Secular variations of fast directions (ϕ) and delay times (dt) between split shear waves are interpreted to sense changing crack densities and pressure. Delay times tend to increase while surface wave velocity decreases before eruptions. Rotations of ϕ may be caused by changes in either stress direction or fluid pressure. These changes usually correlate with GPS baseline changes. Changes in shear wave splitting measurements made on multiplets yield several populations with characteristic delay times, measured incoming polarizations, and fast directions, which change their proportion as a function of time. An eruption sequence on 14 October 2010 yielded over 2000 shear wave splitting measurements in a 14 h period, allowing high time resolution measurements to characterize the sequence. Stress directions from a propagating dike model qualitatively fit the temporal change in splitting.